High-flux self-cleaning composite nanofiber membrane and device thereof
Through high-throughput composite nanofiber membrane, combined with Cu/C-C3N5 photocatalyst, hydrophilic modified materials and PEI coating, the problem of low bilirubin and oil stain removal efficiency in the prior art is solved, and efficient biliary Erobin removal and oil-water separation.
Patent Information
- Application Number
- CN202411723229.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-11-28
AI Technical Summary
The prior art has problems in the removal of bilirubin and oil-water separation and are difficult to operate efficiently under complex operating conditions, especially in oil-containing bilirubin sewage, which is difficult to simultaneously remove bilirubin and oil-filled waste.
High-throughput composite nanofiber membrane is used to modify the spinning liquid by blending and modification method, and the film is prepared by electrospinning method, and the coating is obtained by immersion, including Cu/C-C3N5 photocatalyst and hydrophilic modified materials. and PEI coating to achieve bilirubin removal and oil stain retention.
The bilirubin removal rate is as high as 97.5% and the macromolecular oil retention rate is as high as 99.5%, while maintaining high purity water flux, which is suitable for bilirubin removal and oil-water separation under complex working conditions.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The present invention relates to a high-throughput composite nanofiber membrane and a device for bilirubin removal, belonging to the technical field of separation membrane preparation. The modified membrane has the advantages of high pure water flux, high bilirubin removal efficiency, good oil retention performance and excellent light response effect in the device, and is suitable for the field of bilirubin removal. Background Art
[0002] In today's society, bilirubin removal and oil-water separation are of vital importance in the fields of environmental protection and medicine, respectively. Hyperbilirubinemia poses a threat to human health, especially the nervous system, while bilirubin-containing medical wastewater may seriously pollute soil and groundwater, endangering human health. At the same time, the discharge of oily wastewater also causes serious damage to the water environment. Traditional bilirubin removal and oil-water separation methods have various limitations and are difficult to operate efficiently under complex working conditions.
[0003] Self-cleaning electrospun nanofiber membranes have shown broad application prospects in the fields of bilirubin removal and oil-water separation due to their unique structure given by electrospinning technology. The nanofibers have excellent filtration and adsorption capabilities and can effectively handle difficult problems such as emulsified oil. Their self-cleaning properties can reduce pollutant accumulation, maintain stable performance, extend service life, and reduce maintenance costs. This provides a new technical approach and solution for achieving safe and effective bilirubin removal and efficient and sustainable oil-water separation. However, a series of technical and process challenges still need to be overcome in practical application and promotion.
[0004] At present, the use of nanofiber membranes in the field of bilirubin removal has been studied in depth at home and abroad. Patent CN202110338951.X invented a method for preparing a nanofiber bilirubin adsorbent and a preparation method thereof, which can specifically recognize bilirubin molecules using multiple action sites such as electrostatic adsorption, hydrogen bonding, and Π-Π action. However, research on the removal of bilirubin wastewater and the removal of oil and bilirubin in oil-containing bilirubin wastewater under complex conditions is still insufficient. Therefore, it is necessary to develop a high-throughput composite nanofiber membrane that can effectively remove bilirubin and meet the removal needs of oil pollution at the same time, thereby filling the research gap in this field. Summary of the invention
[0005] The purpose of the present invention is to address the problem that the current membrane is easily contaminated and cannot meet the requirements of membrane separation well. A high-flux composite nanofiber membrane for bilirubin removal is prepared and a device is designed. The prepared hydrophilic modified nanofiber membrane has the advantages of efficient bilirubin removal, high flux, good protein permeability, etc. in the device. It is suitable for the separation process of bilirubin-containing oil and water, and can ensure excellent separation effect and long-term stable operation.
[0006] The high-throughput composite nanofiber membrane for bilirubin removal prepared by the present invention is first modified by a blending modification method, then the spinning solution is prepared by an electrostatic spinning method, and finally a coating is obtained by immersion, comprising the following steps: Step 1): Synthesis of Cu / C-C3N5: Weigh a certain amount of nitrogen-containing organic matter with an analytical balance and dissolve it in a beaker. Use a measuring cylinder to measure an appropriate amount of distilled water and dissolve it in a beaker. Then weigh a certain amount of copper-containing carbon material in a beaker and place it on a magnetic stirrer. Cover the beaker with plastic wrap and stir at room temperature for 3 hours. Then put it in an oven (<80 °C) to completely dry the sample. Weigh the obtained solid sample, grind it with an agate mortar, put it in a crucible, put it in a muffle furnace and heat it to 550 °C. The heating rate is set to 5 °C min -1 Keep the temperature at 550 °C for 3 h. After the reaction is completely cooled, take out the sample, grind it, weigh it, and load it to obtain Cu / C-C3N5. By changing the amount of copper-carbon material and nitrogen-containing organic matter, the mass proportion of copper-carbon material in the total calcined material is 0.5%~5%, thus preparing Cu / C-C3N5 with different proportions.
[0007] Step 2) Preparation of spinning solution: The spinning solution is prepared from two materials according to the following mass percentages. The first material is 8-15% substrate, 6-10% TPU, 1-10% polyvinylpyrrolidone (PVP), 0.5-1% carboxymethyl cellulose (CMC), and the remaining amount is N, N-dimethylformamide. PVP and CMC are dissolved in the solvent and heated and stirred. After dissolution, the substrate and TPU are added and continued to heat and stir for 1.5-3.5 h until completely dissolved. The second material is 11-15% substrate, 4-10% TPU, 0.5-1.5% Cu / C-C3N5, 1-10% PVP, 0.5-1% CMC, and the remaining amount is N, N-dimethylformamide. Cu / C-C3N5 PVP and CMC are dissolved in the solvent and heated and stirred. After dissolution, the substrate and TPU are added and continued to heat and stir for 1.5-3.5 h until completely dissolved.
[0008] Step 3) Preparation of modified membrane: The spinning solution in step (2) is spun into a membrane by electrospinning, the DC voltage of the spinning machine is set to 16-20 KV, the injection pump flow rate is 1.1-1.8 ml / h, and the receiving distance is 16-20 cm. The membrane making process includes two streams of materials being spun in sequence. First, 6-8 ml of the first stream of materials is sucked in and spun for 4-6 h to form a nanofiber base membrane with a membrane thickness of 55-85 μm and a membrane pore size of 0.5-1.5 μm. Then, the spinning solution of the second stream of materials is quickly spun on the formed membrane, 4-6 ml of the second stream of materials is sucked in and spun for 3-4 h to form a PVP, CMC modified Cu / C-C3N5 nanofiber membrane with an overall membrane thickness of 100-130 μm and a membrane pore size of 0.5-1.5 μm. The prepared membrane was then repeatedly washed with an ethanol solution and dried, and the dried membrane was immersed in a PEI solution for 10 min, taken out, and dried for later use.
[0009] Preferably, the calcination time of the nitrogen-containing organic matter in step 1) is 8-10 h.
[0010] Preferably, the material for synthesizing the nitrogen-containing organic matter in step 1) is one or more of 3-amino-1,2,4-triazole, melamine, thiourea, dicyandiamide and urea.
[0011] Preferably, the copper-containing carbon material providing Cu and C in step 1) is one or more of copper glycinate and copper-carbon alloy nanoparticles.
[0012] In the step 2), the substrate is one of polyvinylidene fluoride, polyether sulfone, polyacrylonitrile, polytetrafluoroethylene, polystyrene, cellulose and derivatives thereof.
[0013] Preferably, the aqueous material modifier in step 2) is selected from one or more of carboxymethyl cellulose (CMC), hydrophilic silica nanoparticles (PVP NPs), polyvinyl pyrrolidone (PVP), polyethylene glycol (PEG), and acrylic acid (AA).
[0014] Preferably, the solvent in step 2) is one of N,N-dimethylacetamide, N,N-dimethylformamide, dimethyl sulfoxide, N-methylpyrrolidone, triethyl phosphate, γ-butyrolactone and propylene carbonate.
[0015] Preferably, the imine coating in step 3) is one or more of polyethylene imine, polyamide-imine, and thiobutylamidine chitosan.
[0016] The reaction involved in the degradation of bilirubin involved in the present invention comprises Cu / C-C3N5 photocatalytic degradation of bilirubin, hydrophilic membrane interception of bilirubin and PEI coating adsorption of bilirubin.
[0017] For Cu / C-C3N5 photocatalytic degradation of bilirubin: Under visible light conditions, Cu enhances the light absorption range and realizes charge separation to generate electron-hole pairs. The photogenerated electrons are transferred to the g-C3N5 conduction band, which helps to generate superoxide radicals (O2 - ) and hydroxyl radicals (·OH), thereby converting bilirubin into CO2 and H2O. The addition of carbon materials improves the absorption range and stability of the photocatalyst and prolongs the service life of the photocatalyst.
[0018] For the retention of bilirubin by hydrophilic membranes: The pore size of hydrophilic membranes is moderate, which can retain larger bilirubin molecules. The hydrophilic groups form hydrogen bonds with the hydrophilic groups in the bilirubin molecules, so that the bilirubin molecules are adsorbed on the membrane surface and are difficult to pass through the membrane pores.
[0019] Regarding the adsorption of bilirubin by PEI coating: PEI coating contains positively charged amino and other functional groups, which generate electrostatic attraction with the negative charge of bilirubin, causing bilirubin to be adsorbed on the coating surface.
[0020] The high-flux composite nanofiber membrane for bilirubin removal prepared by the present invention can maintain a pure water flux of 13,000-15,000 L·m under the conditions of bilirubin removal rate ≥ 97.5% and macromolecular oil retention rate ≥ 99.5%. -2 ·h -1 , has significant bilirubin removal and oil droplet separation effects. After multiple bilirubin removal cycles, the nanofiber membrane still maintains excellent performance, providing a reliable solution for efficient bilirubin removal and oil-water separation. Beneficial Effects
[0021] Compared with the prior art, the present invention successfully obtains spinning membranes with different functions based on the continuous multi-step spinning method and the modification of the membrane by obtaining the coating through immersion, and has the following advantages and beneficial effects: 1 High bilirubin removal efficiency. The modified composite nanofiber membrane of the present invention performs well in removing bilirubin, with a removal rate of up to 97.5%. By introducing hydrophilic modified materials and Cu / C-C3N5 modified materials, the pure water flux of the membrane can reach 13000-15000 L·m -2 ·h -1 , which greatly improves the water treatment efficiency and is significantly better than the method of using only photocatalyst to degrade bilirubin.
[0022] 2. Excellent oil retention performance. The modified composite nanofiber membrane has a good oil retention effect and provides a reliable solution for oil-water separation.
[0023] 3. It has self-cleaning and anti-fouling properties, and good long-term operation stability. Through photocatalytic reaction, the nanofiber membrane of the present invention has anti-fouling properties, which prolongs the service life of the membrane. In complex environments, the modified composite nanofiber membrane has higher stability and can effectively cope with challenges in a long-term manner. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 Cu / C-C3N5 in Example 6 of the present invention Figure 2 The present invention is used to test the removal rate of bilirubin by high-throughput composite nanofiber membrane under light Figure 3 Schematic diagram of the structure of the bilirubin-containing oil-water mixture separation device (6) in the device for testing the bilirubin removal rate of the high-throughput composite nanofiber membrane under light illumination of the present invention DETAILED DESCRIPTION
[0025] The present invention is further described below in conjunction with specific embodiments. Example
[0026] Step 1): Synthesis of Cu / C-C3N5: Weigh 1.0 g of 3-AT with an analytical balance and dissolve it in a 25 mL beaker. Use a measuring cylinder to measure 5 mL of distilled water and dissolve it in a beaker. Then weigh 0.02 g of copper glycinate in the beaker and place it on a magnetic stirrer. Cover the beaker with plastic wrap and stir at room temperature for 3 hours. Then put it in an oven (less than 80 °C) to completely dry the sample. Weigh the solid sample, grind it with an agate mortar, put it in a crucible, put it in a muffle furnace and heat it to 550 °C. The heating rate is set to 5 °C min -1 The reaction mixture was kept at 550 °C for 3 h. After the reaction mixture was completely cooled, the sample was taken out, ground, weighed, and loaded. The obtained sample was marked as Cu / C-C3N5.
[0027] After grinding in an agate mortar, the mixture was placed in a crucible and heated to 550 °C in a muffle furnace. The heating rate was set at 5 °C min -1 Keep the temperature at 550 °C for 3 h. After the reaction is completely cooled, take out the sample, grind it, weigh it, and load it to obtain Cu / C-C3N5.
[0028] Step 2): The spinning solution is prepared from two materials according to the following mass percentages of components. The first material is 10% substrate, 5% TPU, 5% PVP, 0.5% CMC, and the rest is solvent. PVP and CMC are dissolved in the solvent and heated and stirred. After dissolution, the substrate and TPU are added and continued to heat and stir for 1.5-3.5 hours until completely dissolved. The second material is 11% substrate, 5% TPU, 1% Cu / C-C3N5, 5% PVP, and 0.5% CMC, and the rest is solvent. Cu / C-C3N5 PVP and CMC are dissolved in the solvent and heated and stirred. After dissolution, the substrate and TPU are added and continued to heat and stir for 1.5-3.5 hours until completely dissolved.
[0029] Step 3) The spinning solution in step (2) is spun into a membrane using an electrospinning method. The DC voltage of the spinning machine is set to 17 KV, the flow rate of the injection pump is 1.5 ml / h, and the receiving distance is 16 cm. The overall membrane preparation process includes two streams of materials being spun in sequence. First, 6 ml of the first stream of material is sucked in and spun for 4-6 h to form a nanofiber base membrane with a membrane thickness of 65 μm and a membrane pore size of 0.6 μm. Then, the spinning solution of the second stream of material is quickly spun on the formed membrane, 3.5 ml of the second stream of material is sucked in and spun for 3-4 h to form a PVP, CMC-modified Cu / C-C3N5 nanofiber membrane with an overall membrane thickness of 100 μm and a membrane pore size of 0.7 μm. Subsequently, the prepared membrane is repeatedly washed with an ethanol solution and dried. The dried membrane is immersed in a PEI solution for 10 min, taken out, and dried for use.
[0030] The pure water flux of the composite nanofiber membrane is 13500 L·m -2 ·h -1 The removal rate of bilirubin is ≥82.8%, the retention rate of macromolecular oil is ≥97.5%, and the effect of separating oil droplets and removing bilirubin is significant. After the bilirubin removal cycle, the nanofiber membrane has excellent bilirubin removal rate and oil retention rate, while its pure water flux remains at a high level. Example
[0031] Step 1): Synthesis of Cu / C-C3N5: Weigh 1.0 g of 3-AT with an analytical balance and dissolve it in a 25 mL beaker. Use a measuring cylinder to measure 5 mL of distilled water and dissolve it in a beaker. Then weigh 0.02 g of copper glycinate in the beaker and place it on a magnetic stirrer. Cover the beaker with plastic wrap and stir at room temperature for 3 hours. Then put it in an oven (less than 80 °C) to completely dry the sample. Weigh the solid sample, grind it with an agate mortar, put it in a crucible, put it in a muffle furnace and heat it to 550 °C. The heating rate is set to 5 °C min -1The reaction mixture was kept at 550 °C for 3 h. After the reaction mixture was completely cooled, the sample was taken out, ground, weighed, and loaded. The obtained sample was marked as Cu / C-C3N5.
[0032] After grinding in an agate mortar, the mixture was placed in a crucible and heated to 550 °C in a muffle furnace. The heating rate was set at 5 °C min -1 Keep the temperature at 550 °C for 3 h. After the reaction is completely cooled, take out the sample, grind it, weigh it, and load it to obtain Cu / C-C3N5.
[0033] Step 2): The spinning solution is prepared from two materials according to the following mass percentages of components. The first material is 10% substrate, 5% TPU, 6% PVP, 0.5% CMC, and the rest is solvent. PVP and CMC are dissolved in the solvent and heated and stirred. After dissolution, the substrate and TPU are added and continued to heat and stir for 1.5-3.5 hours until completely dissolved. The second material is 10% substrate, 5% TPU, 1% Cu / C-C3N5, 6% PVP, and 0.5% CMC, and the rest is solvent. Cu / C-C3N5 PVP and CMC are dissolved in the solvent and heated and stirred. After dissolution, the substrate and TPU are added and continued to heat and stir for 1.5-3.5 hours until completely dissolved.
[0034] Step 3) The spinning solution in step (2) is spun into a membrane using an electrospinning method. The DC voltage of the spinning machine is set to 18 KV, the injection pump flow rate is 1.4 ml / h, and the receiving distance is 17 cm. The overall membrane preparation process includes two streams of materials being spun in sequence. First, 8 ml of the first stream of material is sucked in and spun for 4-6 hours to form a nanofiber base membrane with a membrane thickness of 75 μm and a membrane pore size of 0.7 μm. Then, the spinning solution of the second stream of material is quickly spun on the formed membrane, 6 ml of the second stream of material is sucked in and spun for 3-4 hours to form a PVP, CMC-modified Cu / C-C3N5 nanofiber membrane with an overall membrane thickness of 125 μm and a membrane pore size of 0.8 μm. Subsequently, the prepared membrane is repeatedly washed with an ethanol solution and dried. The dried membrane is immersed in a PEI solution for 10 minutes, taken out, and dried for use.
[0035] The pure water flux of the composite nanofiber membrane is 14000 L·m -2 ·h -1 The removal rate of bilirubin is ≥83.9%, the retention rate of macromolecular oil is ≥99.2%, and the effect of separating oil droplets and removing bilirubin is significant. After the bilirubin removal cycle, the nanofiber membrane has excellent bilirubin removal rate and oil retention rate, while its pure water flux remains at a high level. Example
[0036] Step 1): Synthesis of Cu / C-C3N5: Weigh 1.0 g of 3-AT with an analytical balance and dissolve it in a 25 mL beaker. Use a measuring cylinder to measure 5 mL of distilled water and dissolve it in a beaker. Then weigh 0.02 g of copper glycinate in the beaker and place it on a magnetic stirrer. Cover the beaker with plastic wrap and stir at room temperature for 3 hours. Then put it in an oven (less than 80 °C) to completely dry the sample. Weigh the solid sample, grind it with an agate mortar, put it in a crucible, put it in a muffle furnace and heat it to 550 °C. The heating rate is set to 5 °C min -1 The reaction mixture was kept at 550 °C for 3 h. After the reaction mixture was completely cooled, the sample was taken out, ground, weighed, and loaded. The obtained sample was marked as Cu / C-C3N5.
[0037] After grinding in an agate mortar, the mixture was placed in a crucible and heated to 550 °C in a muffle furnace. The heating rate was set at 5 °C min -1 Keep the temperature at 550 °C for 3 h. After the reaction is completely cooled, take out the sample, grind it, weigh it, and load it to obtain Cu / C-C3N5.
[0038] Step 2): The spinning solution is prepared from two materials according to the following mass percentages of components. The first material is 10% substrate, 5% TPU, 8% PVP, 0.5% CMC, and the rest is solvent. PVP and CMC are dissolved in the solvent and heated and stirred. After dissolution, the substrate and TPU are added and continued to heat and stir for 1.5-3.5 hours until completely dissolved. The second material is 10% substrate, 5% TPU, 1% Cu / C-C3N5, 8% PVP, 0.5% CMC, and the rest is solvent. Cu / C-C3N5 PVP and CMC are dissolved in the solvent and heated and stirred. After dissolution, the substrate and TPU are added and continued to heat and stir for 1.5-3.5 hours until completely dissolved.
[0039] Step 3) The spinning solution in step (2) is spun into a membrane using an electrospinning method. The DC voltage of the spinning machine is set to 19 KV, the injection pump flow rate is 1.4 ml / h, and the receiving distance is 18 cm. The overall membrane preparation process includes two streams of materials being spun in sequence. First, 8 ml of the first stream of material is sucked in and spun for 4-6 hours to form a nanofiber base membrane with a membrane thickness of 85 μm and a membrane pore size of 1.5 μm. Then, the spinning solution of the second stream of material is quickly spun on the formed membrane, 7 ml of the second stream of material is sucked in and spun for 3-4 hours to form a PVP, CMC-modified Cu / C-C3N5 nanofiber membrane with an overall membrane thickness of 130 μm and a membrane pore size of 1.5 μm. Subsequently, the prepared membrane is repeatedly washed with an ethanol solution and dried. The dried membrane is immersed in a PEI solution for 10 minutes, taken out, and dried for use.
[0040] The pure water flux of the composite nanofiber membrane is 13500 L·m-2 ·h -1 The removal rate of bilirubin is ≥86.1%, the retention rate of macromolecular oil is ≥99.3%, and the effect of separating oil droplets and removing bilirubin is significant. After the bilirubin removal cycle, the nanofiber membrane has excellent bilirubin removal rate and oil retention rate, while its pure water flux remains at a high level. Example
[0041] Step 1): Synthesis of Cu / C-C3N5: Weigh 1.0 g of 3-AT with an analytical balance and dissolve it in a 25 mL beaker. Use a measuring cylinder to measure 5 mL of distilled water and dissolve it in a beaker. Then weigh 0.02 g of copper glycinate in the beaker and place it on a magnetic stirrer. Cover the beaker with plastic wrap and stir at room temperature for 3 hours. Then put it in an oven (less than 80 °C) to completely dry the sample. Weigh the solid sample, grind it with an agate mortar, put it in a crucible, put it in a muffle furnace and heat it to 550 °C. The heating rate is set to 5 °C min -1 The reaction mixture was kept at 550 °C for 3 h. After the reaction mixture was completely cooled, the sample was taken out, ground, weighed, and loaded. The obtained sample was marked as Cu / C-C3N5.
[0042] After grinding in an agate mortar, the mixture was placed in a crucible and heated to 550 °C in a muffle furnace. The heating rate was set at 5 °C min -1 Keep the temperature at 550 °C for 3 h. After the reaction is completely cooled, take out the sample, grind it, weigh it, and load it to obtain Cu / C-C3N5.
[0043] Step 2): The spinning solution is prepared from two materials according to the following mass percentages of components. The first material is 10% substrate, 5% TPU, 9% PVP, 0.5% CMC, and the rest is solvent. PVP and CMC are dissolved in the solvent and heated and stirred. After dissolution, the substrate and TPU are added and continued to heat and stir for 1.5-3.5 hours until completely dissolved. The second material is 10% substrate, 5% TPU, 1% Cu / C-C3N5, 9% PVP, 0.5% CMC, and the rest is solvent. Cu / C-C3N5 PVP and CMC are dissolved in the solvent and heated and stirred. After dissolution, the substrate and TPU are added and continued to heat and stir for 1.5-3.5 hours until completely dissolved.
[0044] Step 3) The spinning solution in step (2) is spun into a membrane by electrospinning. The DC voltage of the spinning machine is set to 17 KV, the flow rate of the injection pump is 1.6 ml / h, and the receiving distance is 17 cm. The overall membrane preparation process includes two streams of materials being spun in sequence. First, 7 ml of the first stream of material is sucked in and spun for 4-6 h to form a nanofiber base membrane with a membrane thickness of 75 μm and a membrane pore size of 0.7 μm. Then, the spinning solution of the second stream of material is quickly spun on the formed membrane, 6 ml of the second stream of material is sucked in and spun for 3-4 h to form a PVP, CMC-modified Cu / C-C3N5 nanofiber membrane with an overall membrane thickness of 115 μm and a membrane pore size of 0.8 μm. Subsequently, the prepared membrane is repeatedly washed with an ethanol solution and dried. The dried membrane is immersed in a PEI solution for 10 min, taken out, and dried for use.
[0045] The pure water flux of the composite nanofiber membrane is 14500 L·m -2 ·h -1 The removal rate of bilirubin is ≥91.8%, and the retention rate of macromolecular oil is ≥99.4%. The effect of separating oil droplets and removing bilirubin is remarkable. After the bilirubin removal cycle, the nanofiber membrane has excellent bilirubin removal rate and oil retention rate, while its pure water flux remains at a high level. Example
[0046] Step 1): Synthesis of Cu / C-C3N5: Weigh 1.0 g of 3-AT with an analytical balance and dissolve it in a 25 mL beaker. Use a measuring cylinder to measure 5 mL of distilled water and dissolve it in a beaker. Then weigh 0.02 g of copper glycinate in the beaker and place it on a magnetic stirrer. Cover the beaker with plastic wrap and stir at room temperature for 3 hours. Then put it in an oven (less than 80 °C) to completely dry the sample. Weigh the solid sample, grind it with an agate mortar, put it in a crucible, put it in a muffle furnace and heat it to 550 °C. The heating rate is set to 5 °C min -1 The reaction mixture was kept at 550 °C for 3 h. After the reaction mixture was completely cooled, the sample was taken out, ground, weighed, and loaded. The obtained sample was marked as Cu / C-C3N5.
[0047] After grinding in an agate mortar, the mixture was placed in a crucible and heated to 550 °C in a muffle furnace. The heating rate was set at 5 °C min -1 Keep the temperature at 550 °C for 3 h. After the reaction is completely cooled, take out the sample, grind it, weigh it, and load it to obtain Cu / C-C3N5.
[0048] Step 2): The spinning solution is prepared from two materials according to the following mass percentages of components. The first material is 10% substrate, 5% TPU, 10% PVP, 0.5% CMC, and the rest is solvent. PVP and CMC are dissolved in the solvent and heated and stirred. After dissolution, the substrate and TPU are added and continued to heat and stir for 1.5-3.5 hours until completely dissolved. The second material is 10% substrate, 5% TPU, 1% Cu / C-C3N5, 1% PVP, 0.5% CMC, and the rest is solvent. Cu / C-C3N5 PVP and CMC are dissolved in the solvent and heated and stirred. After dissolution, the substrate and TPU are added and continued to heat and stir for 1.5-3.5 hours until completely dissolved.
[0049] Step 3) The spinning solution in step (2) is spun into a membrane using an electrospinning method. The DC voltage of the spinning machine is set to 20 KV, the injection pump flow rate is 1.4 ml / h, and the receiving distance is 20 cm. The overall membrane preparation process includes two streams of materials being spun in sequence. First, 7 ml of the first stream of material is sucked in and spun for 4-6 h to form a nanofiber base membrane with a membrane thickness of 80 μm and a membrane pore size of 0.6 μm. Then, the spinning solution of the second stream of material is quickly spun on the formed membrane, 5 ml of the second stream of material is sucked in and spun for 3-4 h to form a PVP, CMC-modified Cu / C-C3N5 nanofiber membrane with an overall membrane thickness of 115 μm and a membrane pore size of 0.7 μm. Subsequently, the prepared membrane is repeatedly washed with an ethanol solution and dried. The dried membrane is immersed in a PEI solution for 10 min, taken out, and dried for use.
[0050] The pure water flux of the composite nanofiber membrane is 145000 L·m -2 ·h -1 The removal rate of bilirubin is ≥97.1%, and the retention rate of macromolecular oil is ≥98.5%. The effect of separating oil droplets and removing bilirubin is remarkable. After the bilirubin removal cycle, the nanofiber membrane has excellent bilirubin removal rate and oil retention rate, while its pure water flux remains at a high level. Example
[0051] Step 1): Synthesis of Cu / C-C3N5: Weigh 1.0 g of 3-AT with an analytical balance and dissolve it in a 25 mL beaker. Use a measuring cylinder to measure 5 mL of distilled water and dissolve it in a beaker. Then weigh 0.015 g of copper glycinate in the beaker and place it on a magnetic stirrer. Cover the beaker with plastic wrap and stir at room temperature for 3 hours. Then put it in an oven (less than 80 °C) to completely dry the sample. Weigh the solid sample, grind it with an agate mortar, put it in a crucible, put it in a muffle furnace and heat it to 550 °C. The heating rate is set to 5 °C min -1The reaction mixture was kept at 550 °C for 3 h. After the reaction mixture was completely cooled, the sample was taken out, ground, weighed, and loaded. The obtained sample was marked as Cu / C-C3N5.
[0052] After grinding in an agate mortar, the mixture was placed in a crucible and heated to 550 °C in a muffle furnace. The heating rate was set at 5 °C min -1 Keep the temperature at 550 °C for 3 h. After the reaction is completely cooled, take out the sample, grind it, weigh it, and load it to obtain Cu / C-C3N5.
[0053] Step 2): The spinning solution is prepared from two materials according to the following mass percentages of components. The first material is 10% substrate, 5% TPU, 10% PVP, 0.5% CMC, and the rest is solvent. PVP and CMC are dissolved in the solvent and heated and stirred. After dissolution, the substrate and TPU are added and continued to heat and stir for 1.5-3.5 hours until completely dissolved. The second material is 10% substrate, 5% TPU, 1% Cu / C-C3N5, 1% PVP, 0.5% CMC, and the rest is solvent. Cu / C-C3N5 PVP and CMC are dissolved in the solvent and heated and stirred. After dissolution, the substrate and TPU are added and continued to heat and stir for 1.5-3.5 hours until completely dissolved.
[0054] Step 3) The spinning solution in step (2) is spun into a membrane using an electrospinning method. The DC voltage of the spinning machine is set to 20 KV, the injection pump flow rate is 1.4 ml / h, and the receiving distance is 20 cm. The overall membrane preparation process includes two streams of materials being spun in sequence. First, 7 ml of the first stream of material is sucked in and spun for 4-6 h to form a nanofiber base membrane with a membrane thickness of 75 μm and a membrane pore size of 0.6 μm. Then, the spinning solution of the second stream of material is quickly spun on the formed membrane, 5 ml of the second stream of material is sucked in and spun for 3-4 h to form a PVP, CMC-modified Cu / C-C3N5 nanofiber membrane with an overall membrane thickness of 115 μm and a membrane pore size of 0.65 μm. Subsequently, the prepared membrane is repeatedly washed with an ethanol solution and dried. The dried membrane is immersed in a PEI solution for 10 min, taken out, and dried for use.
[0055] The pure water flux of the composite nanofiber membrane is 150000 L·m -2 ·h -1 The removal rate of bilirubin is ≥97.5%, and the retention rate of macromolecular oil is ≥99.5%. The effect of separating oil droplets and removing bilirubin is remarkable. After the bilirubin removal cycle, the nanofiber membrane has excellent bilirubin removal rate and oil retention rate, while its pure water flux remains at a high level. Example
[0056] Step 1): Synthesis of Cu / C-C3N5: Weigh 1.0 g of 3-AT with an analytical balance and dissolve it in a 25 mL beaker. Use a measuring cylinder to measure 5 mL of distilled water and dissolve it in a beaker. Then weigh 0.01 g of copper glycinate in the beaker and place it on a magnetic stirrer. Cover the beaker with plastic wrap and stir at room temperature for 3 hours. Then put it in an oven (less than 80 °C) to completely dry the sample. Weigh the solid sample, grind it with an agate mortar, put it in a crucible, put it in a muffle furnace and heat it to 550 °C. The heating rate is set to 5 °C min -1 The reaction mixture was kept at 550 °C for 3 h. After the reaction mixture was completely cooled, the sample was taken out, ground, weighed, and loaded. The obtained sample was marked as Cu / C-C3N5.
[0057] After grinding in an agate mortar, the mixture was placed in a crucible and heated to 550 °C in a muffle furnace. The heating rate was set at 5 °C min -1 Keep the temperature at 550 °C for 3 h. After the reaction is completely cooled, take out the sample, grind it, weigh it, and load it to obtain Cu / C-C3N5.
[0058] Step 2): The spinning solution is prepared from two materials according to the following mass percentages of components. The first material is 10% substrate, 5% TPU, 10% PVP, 0.5% CMC, and the rest is solvent. PVP and CMC are dissolved in the solvent and heated and stirred. After dissolution, the substrate and TPU are added and continued to heat and stir for 1.5-3.5 hours until completely dissolved. The second material is 10% substrate, 5% TPU, 1% Cu / C-C3N5, 1% PVP, 0.5% CMC, and the rest is solvent. Cu / C-C3N5 PVP and CMC are dissolved in the solvent and heated and stirred. After dissolution, the substrate and TPU are added and continued to heat and stir for 1.5-3.5 hours until completely dissolved.
[0059] Step 3) The spinning solution in step (2) is spun into a membrane by electrospinning. The DC voltage of the spinning machine is set to 20 KV, the flow rate of the injection pump is 1.4 ml / h, and the receiving distance is 20 cm. The overall membrane preparation process includes two streams of materials being spun in sequence. First, 7 ml of the first stream of material is sucked in and spun for 4-6 h to form a nanofiber base membrane with a membrane thickness of 80 μm and a membrane pore size of 0.6 μm. Then, the spinning solution of the second stream of material is quickly spun on the formed membrane, 5 ml of the second stream of material is sucked in and spun for 3-4 h to form a PVP, CMC modified Cu / C-C3N5 nanofiber membrane with an overall membrane thickness of 125 μm and a membrane pore size of 0.60 μm. Subsequently, the prepared membrane is repeatedly washed with an ethanol solution and dried. The dried membrane is immersed in a PEI solution for 10 min, taken out, and dried for use.
[0060] The pure water flux of the composite nanofiber membrane is 150000 L·m -2 ·h -1 The removal rate of bilirubin is ≥96.5%, and the retention rate of macromolecular oil is ≥97.5%. The effect of separating oil droplets and removing bilirubin is remarkable. After the bilirubin removal cycle, the nanofiber membrane has excellent bilirubin removal rate and oil retention rate, while its pure water flux remains at a high level. Example
[0061] Step 1): Synthesis of Cu / C-C3N5: Weigh 1.0 g of 3-AT with an analytical balance and dissolve it in a 25 mL beaker. Use a measuring cylinder to measure 5 mL of distilled water and dissolve it in a beaker. Then weigh 0.15 g of copper glycinate in a beaker and place it on a magnetic stirrer. Cover the beaker with plastic wrap and stir at room temperature for 3 hours. Then put it in an oven (less than 80 °C) to completely dry the sample. Weigh the solid sample, grind it with an agate mortar, put it in a crucible, put it in a muffle furnace and heat it to 550 °C. The heating rate is set to 5 °C min -1 The reaction mixture was kept at 550 °C for 3 h. After the reaction mixture was completely cooled, the sample was taken out, ground, weighed, and loaded. The obtained sample was marked as Cu / C-C3N5.
[0062] After grinding in an agate mortar, the mixture was placed in a crucible and heated to 550 °C in a muffle furnace. The heating rate was set at 5 °C min -1 Keep the temperature at 550 °C for 3 h. After the reaction is completely cooled, take out the sample, grind it, weigh it, and load it to obtain Cu / C-C3N5.
[0063] Step 2): The spinning solution is prepared from two materials according to the following mass percentages of components. The first material is 8% substrate, 5% TPU, 10% PVP, 0.5% CMC, and the rest is solvent. PVP and CMC are dissolved in the solvent and heated and stirred. After dissolution, the substrate and TPU are added and continued to heat and stir for 1.5-3.5 hours until completely dissolved. The second material is 8% substrate, 5% TPU, 1% Cu / C-C3N5, 1% PVP, 0.5% CMC, and the rest is solvent. Cu / C-C3N5 PVP and CMC are dissolved in the solvent and heated and stirred. After dissolution, the substrate and TPU are added and continued to heat and stir for 1.5-3.5 hours until completely dissolved.
[0064] Step 3) The spinning solution in step (2) is spun into a membrane using an electrospinning method. The DC voltage of the spinning machine is set to 20 KV, the injection pump flow rate is 1.6 ml / h, and the receiving distance is 19 cm. The overall membrane preparation process includes two streams of materials being spun in sequence. First, 7 ml of the first stream of material is sucked in and spun for 4-6 h to form a nanofiber base membrane with a membrane thickness of 85 μm and a membrane pore size of 0.7 μm. Then, the spinning solution of the second stream of material is quickly spun on the formed membrane, 6 ml of the second stream of material is sucked in and spun for 3-4 h to form a PVP, CMC-modified Cu / C-C3N5 nanofiber membrane with an overall membrane thickness of 120 μm and a membrane pore size of 0.9 μm. Subsequently, the prepared membrane is repeatedly washed with an ethanol solution and dried. The dried membrane is immersed in a PEI solution for 10 min, taken out, and dried for use.
[0065] The pure water flux of the composite nanofiber membrane is 14000 L·m -2 ·h -1 The removal rate of bilirubin is ≥89.5%, and the retention rate of macromolecular oil is ≥95.5%. The effect of separating oil droplets and removing bilirubin is remarkable. After the bilirubin removal cycle, the nanofiber membrane has excellent bilirubin removal rate and oil retention rate, while its pure water flux remains at a high level. Example
[0066] Step 1): Synthesis of Cu / C-C3N5: Weigh 1.0 g of 3-AT with an analytical balance and dissolve it in a 25 mL beaker. Use a measuring cylinder to measure 5 mL of distilled water and dissolve it in a beaker. Then weigh 0.15 g of copper glycinate in a beaker and place it on a magnetic stirrer. Cover the beaker with plastic wrap and stir at room temperature for 3 hours. Then put it in an oven (less than 80 °C) to completely dry the sample. Weigh the solid sample, grind it with an agate mortar, put it in a crucible, put it in a muffle furnace and heat it to 550 °C. The heating rate is set to 5 °C min -1 The reaction mixture was kept at 550 °C for 3 h. After the reaction mixture was completely cooled, the sample was taken out, ground, weighed, and loaded. The obtained sample was marked as Cu / C-C3N5.
[0067] After grinding in an agate mortar, the mixture was placed in a crucible and heated to 550 °C in a muffle furnace. The heating rate was set at 5 °C min -1 Keep the temperature at 550 °C for 3 h. After the reaction is completely cooled, take out the sample, grind it, weigh it, and load it to obtain Cu / C-C3N5.
[0068] Step 2): The spinning solution is prepared from two materials according to the following mass percentages of components. The first material is 10% substrate, 5% TPU, 10% PVP, 0.5% CMC, and the rest is solvent. PVP and CMC are dissolved in the solvent and heated and stirred. After dissolution, the substrate and TPU are added and continued to heat and stir for 1.5-3.5 hours until completely dissolved. The second material is 10% substrate, 5% TPU, 0.5% Cu / C-C3N5, 10% PVP, 0.5% CMC, and the rest is solvent. Cu / C-C3N5 PVP and CMC are dissolved in the solvent and heated and stirred. After dissolution, the substrate and TPU are added and continued to heat and stir for 1.5-3.5 hours until completely dissolved.
[0069] Step 3) The spinning solution in step (2) is spun into a membrane using an electrospinning method. The DC voltage of the spinning machine is set to 20 KV, the flow rate of the injection pump is 1.4 ml / h, and the receiving distance is 20 cm. The overall membrane preparation process includes two streams of materials being spun in sequence. First, 7 ml of the first stream of material is sucked in and spun for 4-6 h to form a nanofiber base membrane with a membrane thickness of 70 μm and a membrane pore size of 0.65 μm. Then, the spinning solution of the second stream of material is quickly spun on the formed membrane, 5 ml of the second stream of material is sucked in, and spun for 3-4 h to form a PVP, CMC-modified Cu / C-C3N5 nanofiber membrane with an overall membrane thickness of 110 μm and a membrane pore size of 0.7 μm. Subsequently, the prepared membrane is repeatedly washed with an ethanol solution and dried. The dried membrane is immersed in a PEI solution for 10 min, taken out, and dried for use.
[0070] The pure water flux of the composite nanofiber membrane is 13500 L·m -2 ·h -1 The removal rate of bilirubin is ≥86.5%, the retention rate of macromolecular oil is ≥98.9%, and the effect of separating oil droplets and removing bilirubin is significant. After the bilirubin removal cycle, the nanofiber membrane has excellent bilirubin removal rate and oil retention rate, while its pure water flux remains at a high level. Example
[0071] Step 1): Synthesis of Cu / C-C3N5: Weigh 1.0 g of 3-AT with an analytical balance and dissolve it in a 25 mL beaker. Use a measuring cylinder to measure 5 mL of distilled water and dissolve it in a beaker. Then weigh 0.15 g of copper glycinate in a beaker and place it on a magnetic stirrer. Cover the beaker with plastic wrap and stir at room temperature for 3 hours. Then put it in an oven (less than 80 °C) to completely dry the sample. Weigh the solid sample, grind it with an agate mortar, put it in a crucible, put it in a muffle furnace and heat it to 550 °C. The heating rate is set to 5 °C min -1The reaction mixture was kept at 550 °C for 3 h. After the reaction mixture was completely cooled, the sample was taken out, ground, weighed, and loaded. The obtained sample was marked as Cu / C-C3N5.
[0072] After grinding in an agate mortar, the mixture was placed in a crucible and heated to 550 °C in a muffle furnace. The heating rate was set at 5 °C min -1 Keep the temperature at 550 °C for 3 h. After the reaction is completely cooled, take out the sample, grind it, weigh it, and load it to obtain Cu / C-C3N5.
[0073] Step 2): The spinning solution is prepared from two materials according to the following mass percentages of components. The first material is 10% substrate, 5% TPU, 10% PVP, 0.5% CMC, and the rest is solvent. PVP and CMC are dissolved in the solvent and heated and stirred. After dissolution, the substrate and TPU are added and continued to heat and stir for 1.5-3.5 hours until completely dissolved. The second material is 10% substrate, 5% TPU, 1.5% Cu / C-C3N5, 10% PVP, 0.5% CMC, and the rest is solvent. Cu / C-C3N5 PVP and CMC are dissolved in the solvent and heated and stirred. After dissolution, the substrate and TPU are added and continued to heat and stir for 1.5-3.5 hours until completely dissolved.
[0074] Step 3) The spinning solution in step (2) is spun into a membrane using an electrospinning method. The DC voltage of the spinning machine is set to 20 KV, the flow rate of the injection pump is 1.4 ml / h, and the receiving distance is 20 cm. The overall membrane preparation process includes two streams of materials being spun in sequence. First, 7 ml of the first stream of material is sucked in and spun for 4-6 hours to form a nanofiber base membrane with a membrane thickness of 75 μm and a membrane pore size of 0.5 μm. Then, the spinning solution of the second stream of material is quickly spun on the formed membrane, 5 ml of the second stream of material is sucked in and spun for 3-4 hours to form a PVP, CMC-modified Cu / C-C3N5 nanofiber membrane with an overall membrane thickness of 120 μm and a membrane pore size of 0.7 μm. Subsequently, the prepared membrane is repeatedly washed with an ethanol solution and dried. The dried membrane is immersed in a PEI solution for 10 minutes, taken out, and dried for use.
[0075] The pure water flux of the composite nanofiber membrane is 15000 L·m -2 ·h -1 The removal rate of bilirubin is ≥92.4%, and the retention rate of macromolecular oil is ≥98.5%. The effect of separating oil droplets and removing bilirubin is remarkable. After the bilirubin removal cycle, the nanofiber membrane has excellent bilirubin removal rate and oil retention rate, while its pure water flux remains at a high level. Example
[0076] Step 1): The spinning solution is prepared from two materials according to the following mass percentages of components: the first material is 10% substrate, 5% TPU, 10% PVP, 0.5% CMC, and the rest is solvent. PVP and CMC are dissolved in the solvent and heated and stirred. After dissolution, the substrate and TPU are added and continued to heat and stir for 1.5-3.5 hours until completely dissolved. The second material is 10% substrate, 5% TPU, 10% PVP, 0.5% CMC, and the rest is solvent. Cu / C-C3N5 PVP and CMC are dissolved in the solvent and heated and stirred. After dissolution, the substrate and TPU are added and continued to heat and stir for 1.5-3.5 hours until completely dissolved.
[0077] Step 3) The spinning solution in step (2) is spun into a membrane using an electrospinning method. The DC voltage of the spinning machine is set to 20 KV, the injection pump flow rate is 1.4 ml / h, and the receiving distance is 20 cm. The overall membrane preparation process includes two streams of materials being spun in sequence. First, 7 ml of the first stream of material is sucked in and spun for 4-6 h to form a nanofiber base membrane with a membrane thickness of 75 μm and a membrane pore size of 0.5 μm. Then, the spinning solution of the second stream of material is quickly spun on the formed membrane, 5 ml of the second stream of material is sucked in and spun for 3-4 h to form a PVP, CMC-modified Cu / C-C3N5 nanofiber membrane with an overall membrane thickness of 120 μm and a membrane pore size of 0.5 μm. The prepared membrane is then repeatedly washed with an ethanol solution and dried.
[0078] The pure water flux of the double-layer nanofiber membrane is 12000 L·m -2 ·h -1 , the removal rate of bilirubin is ≥30.4%, and the retention rate of macromolecular oil is ≥94.5%. After the bilirubin removal cycle, its pure water flux is greatly reduced.
Claims
1. A high-throughput composite nanofiber membrane for bilirubin removal, characterized in that: The following steps are involved: (1) Synthesis of Cu / C-C3N5: A certain amount of nitrogen-containing organic matter and a certain amount of copper-containing carbon material are fully stirred, the reactants are dried, ground and calcined, and after cooling, the samples are taken out, ground, weighed and loaded to obtain Cu / C-C3N5. The amount of copper-containing carbon material and nitrogen-containing organic matter is changed, and the mass proportion of copper-carbon material in the total calcined material is 0.5%~5%, thereby preparing Cu / C-C3N5 with different proportions; (2) Preparation of spinning solution: The spinning solution is prepared from two materials according to the following mass percentages: the first material is 8-15% substrate, 6-10% TPU, 1-10% polyvinylpyrrolidone (PVP), 0.5-1% carboxymethyl cellulose (CMC), and the remainder is N,N-dimethylformamide. PVP and CMC are dissolved in a solvent and heated and stirred. After dissolution, the substrate and TPU are added and heated and stirred for 1.5-3.5 h until completely dissolved. The second material is 11-15% substrate, 4-10% TPU, 0.5-1.5% Cu / C-C3N5, 1-10% PVP, 0.5-1% CMC, and the remainder is N,N-dimethylformamide. Cu / C-C3N5 PVP and CMC are dissolved in a solvent and heated and stirred. After dissolution, the substrate and TPU are added and heated and stirred for 1.5-3.5 h until completely dissolved; (3) Preparation of high-throughput composite nanofiber membrane for bilirubin removal: The spinning solution in step (2) is spun into a membrane using an electrospinning method. The DC voltage of the spinning machine is set to 16-20 KV, the flow rate of the injection pump is 1.1-1.8 ml / h, and the receiving distance is 16-20 cm. The membrane preparation process includes two streams of materials being spun in sequence. First, 6-8 ml of the first stream of materials are sucked in and spun for 4-6 hours to form a nanofiber base membrane with a membrane thickness of 55-85 μm and a membrane pore size of 0.5-1.5 μm. Then, the spinning solution of the second stream of materials is quickly spun on the formed membrane, 4-6 ml of the second stream of materials are sucked in and spun for 3-4 hours to form a PVP, CMC-modified Cu / C-C3N5 nanofiber membrane with an overall membrane thickness of 100-130 μm and a membrane pore size of 0.5-1.5 μm. The prepared membrane is then repeatedly washed with an ethanol solution and dried, and the dried membrane is immersed in a PEI solution for 10 minutes, taken out, and dried for use.
2. According to the preparation of the spinning solution in claim 1: the hydrophilic material modifier is selected from one or more of carboxymethyl cellulose (CMC), silicon dioxide (SiO2), polyvinyl pyrrolidone (PVP), polyethylene glycol (PEG), and acrylic acid (AA); the substrate is one of polyvinylidene fluoride, polyether sulfone, polyacrylonitrile, polytetrafluoroethylene, polystyrene, cellulose and its derivatives; the solvent is one of N,N-dimethylacetamide, N,N-dimethylformamide, dimethyl sulfoxide, N-methylpyrrolidone, triethyl phosphate, γ-butyrolactone, and propylene carbonate; the imine coating is one or more of polyethylene imine, polyamide-imine, and thiobutylamidine chitosan.
3. The method for preparing a high-throughput composite nanofiber membrane for bilirubin removal according to claim 1, characterized in that: The nitrogen-containing organic matter for synthesizing the Cu / C-C3N5 modifier is one or more of 3-amino-1,2,4-triazole, melamine, thiourea, dicyandiamide and urea; wherein the copper-containing carbon material is one or more of cuprous glycinate, copper glycinate, Prussian blue and copper-carbon alloy nanoparticles.
4. A method for preparing a high-throughput composite nanofiber membrane for bilirubin removal according to any one of claims 1 to 3, wherein the prepared high-throughput composite nanofiber membrane for bilirubin removal is characterized in that: The pure water flux of the composite nanofiber membrane is 13000-15000 L·m -2 ·h -1 The removal rate of bilirubin is ≥97.5%, and the retention rate of macromolecular oil is ≥99.5%.
5. A high-throughput composite nanofiber membrane for bilirubin removal and a device thereof. According to the transport route of the oil-water mixture containing bilirubin, the device comprises a bilirubin-containing oil-water mixture feed tank (1), a pump (2), a pressure gauge (3), a speed control meter (4), a xenon lamp (5), a bilirubin-containing oil-water mixture separation device (6), an oil and dirt storage tank (7), a valve (8), and a purified liquid storage tank (9).
6. A high-throughput composite nanofiber membrane and device for bilirubin removal according to claim 8, characterized in that: The pump (2) draws the bilirubin-containing oil-water mixture from the bilirubin-containing oil-water mixture feed tank (1), and after being adjusted by the pressure gauge (3) and the speed control meter (4), the mixture is irradiated by a xenon lamp (5) for photochemical reaction, and then separated by the bilirubin-containing oil-water mixture separation device (6). The intercepted liquid enters the oil storage tank (7), and the permeate flows into the closed bilirubin-containing oil-water mixture feed tank (1). After the experiment is completed, the valve (8) is opened to collect the treated solution in the purified liquid storage tank (9). This process forms a circulatory system that allows for efficient removal of bilirubin.
7. A high-throughput composite nanofiber membrane and device for bilirubin removal according to claim 8, wherein the device comprises a bilirubin-containing oil-water mixture separation device (6): as shown in FIG3 , a groove is cut on the top of a conventional stainless steel oil-water separation device (10), and a cutoff filter (11) (compressive strength > 3 MPa) greater than 420 nm is fixed thereon with JA-1160 epoxy AB glue (compressive strength > 50 MPa).
8. A device for measuring the performance of a high-throughput composite nanofiber membrane for bilirubin removal according to claims 5-7: the bilirubin interception and oil-water separation device (6) can withstand a maximum pressure of 3 MPa, and when transporting an oil-water mixture containing bilirubin, the pressure should be lower than 3 MPa.
Citation Information
Patent Citations
Nanofiber bilirubin adsorbent and preparation method thereof
CN112941655A
Photocatalysis degradation sewage device and sewage degradation method
CN102010025A
Oil-water emulsion separation method and filter membrane for oil-water emulsion separation
CN108516607A
Patterned porous nano-fiber material with double functions of oil and water separation and oil pollution resistance and preparation method and application of patterned porous nano-fiber material
CN109432825A
High-stability ceramic-based sub-nanopore graphene composite membrane and precise separation application
CN115920667A